Investigating the impact of seasonal temperature variation on biogas production from covered anaerobic lagoons treating slaughterhouse wastewater using lab scale studies. Issue 3 (June 2019) - Schmidt, Thomas; Harris, Peter; Lee, Seonmi; McCabe, Bernadette K.
Abstract: Low-rate anaerobic digestion technology can be influenced by environmental conditions, most notably temperature. The effect of temperature on lipid degradation and crust formation in lagoon digesters treating red meat processing (RMP) wastewater is especially pronounced, impacting on the anaerobic digestion process, resulting degradation and biogas generation. This study investigates the effect of temperature reduction from 38 °C to 25 °C to simulate the annual seasonal temperature range experienced in a covered anaerobic lagoon treating slaughterhouse wastewater located in South-East Queensland, Australia. A step-wise temperature reduction was carried out over a three-month period in continuous stirred tank reactors, and anaerobic digestion performance was compared to digesters operating at optimal mesophilic conditions. After reaching the minimum seasonal temperature, the organic loading rate was increased to identify the limits for organic loading at the different temperature levels. Lower temperatures had a negative impact on degradation efficiency, biogas production, and process stability. The translation of lab scale results to commercial scale operation indicated a 30% reduction in biogas production at a temperature of 31 °C, which corresponded to the highest annual temperatures in the covered anaerobic lagoon. A further decrease to 25.5 °C, which represents the lowest annual temperature in the lagoon, with an increase of the organic loading rate caused up to 80% difference in gas production and negatively influenced process stability. Economic assessment indicated that by operating lagoons under optimal mesophilic conditions, natural gas consumption could be offset with biogas to reduce yearly expenditure of natural gas by up to 25.4%.